Shoulder Dystocia during Delivery and Long-Term Neurological Morbidity of the Offspring - Harari, Ziv; Zamstein, Omri; Sheiner, Eyal; Wainstock, Tamar (American Journal of Perinatology, 2019)
Objective The study aimed to evaluate risk factors and implications of shoulder dystocia (SD) on the neurological outcome of successfully delivered offspring.Study Design This is a cohort analysis including 207,571 deliveries. Risk factors for SD were evaluated using general estimation equation multivariable analyses. Offspring hospitalization incidence up to age 18 years due to neurological conditions was compared between both groups. Kaplan–Meyer curve was used to assess the cumulative hospitalization incidence. Cox proportional hazards model was used to control for confounders.Results SD complicated 0.2% (n = 353) of deliveries included in the study (n = 207,571). Risk factors for SD were fetal macrosomia, maternal diabetes mellitus, male gender, and advanced maternal age (p < 0.05 for all). Higher perinatal mortality was observed among SD cases (2.8 vs. 0.4%, p < 0.001). In most of the investigated neurological conditions no significant differences were found between the groups. Comparable rates of cumulative neurological-related hospitalization were observed (log rank p-value = 0.342) as well as lack of association between SD and neurological hospitalization (adjusted HR = 0.73; 95% CI 0.36–1.47; p = 0.381) when controlled for gestational age.Conclusion Risk factors for SD are macrosomia, diabetes mellitus, male gender, and advanced maternal age. SD is not associated with long-term neurological morbidity of the offspring.
Keywords: shoulder dystocia; neurological; risk factors; hospitalizations; offspring